(414) A Diagrammatic Representation of the Policy of Accounting Prices تمثيل تخطيطي لسياسة أسعار المحاسبة - Qayum, A. (معهد التخطيط القومى, 2024)
This study examines the concept of accounting prices as an economic instrument designed to achieve the optimal allocation of productive resources and guide economic decisions toward maximizing social and economic welfare. The research aims to provide a diagrammatic and analytical representation of accounting price policy and to explain its role in addressing structural imbalances commonly observed in developing economies, particularly those associated with inefficient resource allocation. The study defines accounting prices as estimated values assigned to production factors in such a way that cost calculations based on these values lead producers toward selecting optimal technologies and production techniques. Such a process contributes to maximizing national output under existing resource constraints and societal preferences. The study emphasizes that accounting prices differ from prevailing market prices because they are intended to correct market distortions and improve economic efficiency. The paper further analyzes the conditions of developing economies, which often experience a shortage of capital accompanied by a relatively abundant labor supply. Several factors are identified as contributors to this structural imbalance, including rapid population growth, low domestic savings rates, cheap credit policies, and institutional rigidities affecting factor utilization. Using graphical and analytical models, the research demonstrates the relationship between factor proportions and production possibilities. It explains how accounting prices can encourage producers to adopt more efficient technologies that correspond more closely with the actual availability of production resources within the economy. The study argues that reliance solely on market prices may generate inefficient resource allocation and prevent the economy from reaching its potential level of output. The academic significance of the study lies in its integration of economic theory with practical planning applications. It offers a systematic analytical framework that contributes to better policy formulation and supports decision-making processes aimed at achieving efficient utilization of available resources in developing economies.